Hematological characterization of compound heterozygous hemoglobin Hope/E patients with and without α-Thalassemia-1 SEA type deletion - Sakorn Pornprasert (2018)
Background: There is no report of hematological data in patients with co-inheritance of compound heterozygous hemoglobin (Hb) Hope/E and α-thalassemia-1 Southeast Asian (SEA) type deletion. Methods: Hematological parameters were studied in 3 Thai patients with compound heterozygous Hb Hope/E and 1 of them had α-thalassemia-1 SEA type deletion. Red cell counts, hemoglobin, hematocrit, and red cell indices were measured using an automated blood counter. The molecular analysis of Hb Hope was performed using the amplification refractory mutation system (ARMS)-PCR. Results: The lowest levels of hemoglobin, hematocrit, MCV, MCH, and HbA 2 /E and the highest level of RDW were found in a patient who had co-inheritance of compound heterozygous Hb Hope/E and a-thalassemia-1 SEA type deletion. Conclusions: Co-inheritance of compound heterozygous Hb Hope/E and α-thalassemia-1 SEA type deletion caused prominent changes in hematological features. Thus, knowledge and understanding of these multiple gene interactions will assist in diagnosis, management, and counseling in these patients.